Variation of Received Signal Strength in Wireless Sensor Network - Lisheng Xu; Feifei Yang; Yuqi Jiang; Lei Zhang; Cong Feng; Nan Bao (2011 3rd International Conference on Advanced Computer Control, 2011)
Semiconductor manufacturers provide low-cost, low-power and short-range solutions for the application of Wireless Sensor Network (WSN), such as ZigBee, Bluetooth, Wi-Fi etc. The quality of radio frequency signal, which carries information in wireless communication channel, is the key to WSN. But it is easily influenced by the external environment. Received Signal Strength Indicator (RSSI) is a measurement for the quality of radio frequency signal which is often used in field of space localization. This paper comprehensively analyses the characteristics of RSSI possibly influenced by the factors such as temperature, the height of sensor node's position, the type of antenna and the electromagnetic interference of human body. We found that the attenuation of Received Signal Strength (RSS) varies about 5.0 dBm with the change of temperature in every 10 centigrade. The ground can reduce the radiation area of wireless signal, so that RSS is dramatically influenced by the height of its position. Patch antenna causes the attenuation of RSS about 11.2 dBm larger than helix antenna in the distance of 25 m. If the sensor node is wore in human body, the posterior position leads to the attenuation of RSS about 13.0~16.2 dBm larger than anterior position in a specified distance range due to the electromagnetic interference of human body. Finally, some improvement devices were raised here for the WSN in the application of home healthcare according to the qualified effects of various environmental factors.